Research on CLLLC Resonant Bidirectional DC-DC Converter. Issue 1 (August 2021) - Lei, Hou; Huizhuo, Ma; Xingyu, Chen; Kang, Zhang
Abstract: Based on the single-phase full-bridge LLC DC-DC converter, the LC series resonant network is introduced in the secondary side of the high frequency transformer to form the bidirectional CLLLC resonant DC-DC converter. Firstly, the bidirectional CLLLC resonant DC-DC converter was used for mathematical modeling. By extending the description function, the large-signal steady-state model of the converter was obtained, and the DC voltage gain when the DC-DC converter was running forward was deduced. The gain characteristics and frequency characteristics of the model are compared with those of the basic wave equivalent model. Secondly, the small-signal perturbation model of CLLLC DC-DC converter is modeled, and the small-signal perturbation is brought into the large-signal steady-state solution to obtain the transfer function when the CLLLC resonant converter is running forward. Finally, a 20kW CLLLC DC-DC converter is designed, and the simulation analysis is carried out to verify the correctness of the proposed scheme.